How Jane Austen Uses Marriage to Get What She Wants - Hannah Eberle (Pursuit - The Journal of Undergraduate Research at the University of Tennessee, 2011)
As a biochemistry major approaching the subject of Jane Austen and feminism, I found the dichotomy between pleasure readers and critical readers interesting. How can books that are almost 200 years old draw so much attention from both quarters still today? In my thesis, I use Sense and Sensibility, Pride and Prejudice, and Emma to discuss how Austen uses the marriage plot in the context of the 18th century. This plot device allows her to point out problems with marriage as a market, such as emphasis on wealth and the social setup that requires women to be "taken care of" by men. Her strategy works because it is a mixture of the pleasurable and the critical: one cannot read Austen without enjoying the romantic love stories and learning deeper lessons. This intriguing overlap is one of the reasons Austen continues to impact the modern world.
Keywords: Jane Austen; Marriage